The Islamic view of Jesus: (peace be upon him) - Kathir, Ibn (Islamic Book Service New Delhi, 2006)
The Islamic View of Jesus (Peace Be Upon Him) explores Jesus's revered status in Islam, highlighting his prophethood, miracles, and role within Islamic theology, distinct from Christian beliefs.